Estimation of direct and maternal effects for weaning and yearling weight in Bali cattle - Lisa Praharani (Indonesian Center for Animal Research and Development (ICARD), 2007)
Growth trait is a function of its inherent ability for growth, milk production and mothering ability of its dam. A study was conducted to investigate the effects of maternal on the genetic evaluation of Bali cattle. There were 8.320 calves used to analyze genetik parameters affecting W205 and W365. A connectedness program was used to evaluate genetik linkages between contemporary groups (CG). Data were analyzed to observe non-genetik factors using PROC MIXED (SAS). Single and multiple trait analyses were done including CG, sex of calf and dam age as fixed effects. Variance components were computed by the ASREML package using animal models BLUP with matrix inverse of relationship. A sequential analysis was performed by including additional random effect to evaluate the inclusion of maternal effects, which were compared using likelihood-ratio tests (LRT). Estimates of direct and maternal effects of single-trait and multiple-traits were different. Heritability for W205-D, W365-D, W205-M, W365-M were 0.31; 0.48; 0.08 and 0.01, respectively. Negatif correlation between direct and maternal effects for both W205-DM and W365-DM were quite moderate. Although the estimates of maternal effects in Bali cattle were low; the inclusion of maternal effects has to be considered due to moderate correlation between direct and maternal effects in order to obtain accurate genetic variances. Key Words: Maternal Effects, Heritability, Live Weights, Bali Cattle